Effects of different hydrogen concentrations on rhizosphere bacteria of soybean (Glycine max L.) (Bangladesh Journal of Botany, 2021)
Effects of hydrogen concentrations on the diversity and changes of bacterial community structure, soybean rhizosphere soil samples were investigated. The high-throughput sequencing technology of illumina was adopted to determine the bacterial 16S rRNA V3+V4 region series. Data processing such as splicing, filtering, removing chimeric sequences, and cluster analysis was then performed based on the raw data, and the tax was annotated with OTU. When the air-treated soil samples were compared with the ones treated with hydrogen at a concentration of 1100 ppm and 1300 ppm, the abundance of Proteobacteria increased and Actinobacteria decreased for the later. In addition the Simpson index decreased and the Shannon index increased significantly for both hydrogen-treated samples. However, for the soil sample treated with 1500 ppm of hydrogen, the above-mentioned two indexes didnot vary obviously compared with the air-treated sample. The results demonstrated that the rhizosphere bacterial structure diversity of soybean was significantly increased after hydrogen treatment at the concentration of 1100 and 1300 ppm.Bangladesh J. Bot. 50(3): 775-780, 2021 (September) Special